Parastatals as instruments of government policy: The Food Corporation of India. (December 2016) - McCorriston, Steve; MacLaren, Donald
Highlights: The FCI is the means through which livelihood and food security is sought. These objectives can still be achieved while reducing the role of the FCI. The TPDS and the MSP lead to losses which can avoided through re-instrumentation. Cash transfers and a guaranteed price/deficiency payment replace the TPDS and MSP. This change allows greater participation by more efficient private intermediaries. Significant increases in social welfare are achieved yet with unchanged objectives. Abstract: Reforms of agri-food policies typically occur without taking account of the structure of markets in which the policy reforms occur. It is usually assumed that markets are perfectly competitive, an assumption that is violated in the presence of parastatals. They often play multiple roles in meeting the objectives of government policy through their activities in procurement and distribution of food commodities. After presenting a general framework, we modify it to model the specifics of the Food Corporation of India and the functions that it fulfils in providing price support to farmers and food security to poor households. Keeping the government's policy objectives unchanged, we then alter the functions that the FCI fulfils to be consistent with recommendations from the High Level Committee that recently investigated the role of the FCI. These recommendations included the substitution of negotiable warehouse receipts for the Minimum Support Price scheme for farmers, and the substitution of cash transfers in place of the Targeted Public Distribution System for poor households. We find that this re-instrumentation of the means of achieving policy objectives, together with a consequent greater role for the private sector, leads to substantial welfare gains as well as to greater food security when measured as food availability.